2022-RA-1509-ESGO The MULTISENT study: Analysis of survival according to the volume of sentinel lymph node disease. (20th October 2022) - Cabrera, Silvia; Gomez-Hidalgo, Natalia R; Garcia-Pineda, Virginia; Bebia, Vicente; Fuste, Pere; Alonso, Paula; Fargas, Francesc; Fernández, Sergi; Padilla-Iserte, Pablo; Gómez-Rodríguez, Tomas; Oliver, Reyes; Chacón, Enrique; et al.
Abstract : Introduction/Background: The MULTISENT study is an initiative that aims to analyze the clinical application of sentinel lumph-node(SLN) technique in Spain. This abstract presents the second objective of the study, aiming to evaluate the rate of SLN metastases detected and the impact of the volume of the disease on the survival of the patients. Methodology: Multicenter retrospective study in which twenty-nine Spanish centers were enrolled. Patients operated between 2015–2021 with preoperative clinical stage I-II EC and undergoing SLN mapping as part of their surgical protocol were included. SLN mapping was performed with three different tracers(ICG, ICG + 99mTC and 99mTC alone or in combination with blue dyes) and different sites of injections were used(cervical, uterus and both). Pelvic lymphadenectomy was performed in 54% of the cohort and aortic lymphadenectomy in 26%, according to the preoperative risk of the patient and the institutional protocol. OSNA or ultra-staging protocols with immunohistochemistry were used to study SLN specimens. Results: 1182 eligible patients were analyzed. Median age was 62.7 y(55.9–70.5 y). Median number of resected SLNs was 2(range 1–3) per patient. Minimally-invasive surgeries were performed in 1127(95%) patients. 117 patients(9.9%) had positive SLNs, 68 patients(5.7%) with macrometastases and 49(4.2%) with low-volume disease(24 micrometastases and 25 isolated tumour cells, ITC). Patients with macrometastases had a significantly higher proportion of non-endometrioid histologies, grade 3, lymph-vascular invasion, and received more extensive surgery and adjuvant chemotherapy. False-negative rate(FNR) of the SLN technique in the cohort was 1.6%. With a median follow up of 1.8 y(0.9–3 y), patients with macrometastases in SLN showed a decreased overall survival(OS) and disease-free survival(DFS) when compared to patients with negative SLN, ITC or micrometastases ( figure1 ). Conclusion: SLN is a feasible technique with high sensitivity and low false-negative rate. Patients with macrometastasis showed the worst results in terms of OS and DFS.